Invective vocabulary in social media - Mettibayeva, С.А.; Dossymbekova, Р.О. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
Today, a vivid manifestation of linguistic pragmatics is an invective strategy, which is actively used, especially by users of social networks. The article analyzes the opinions of Instagram users from the point of view of the manifestation of linguistic aggression, which, according to the author of the article, is explained, on the one hand, by the specifics of Internet communication, i.e. it lacks a number of communicative limitations, the virtual nature of communication prevails and anonymity, on the other hand, is a sign of social tension: the level of verbal aggression is determined by the level of interest in the content of the publication, i.e. what is reflected in the text directly depends on the importance of the event for the commentator. The purpose of the article is to identify the main types and functions of invective vocabulary in the texts of comments written by users of social networks to short posts in which the news of the country is published. It is noted that the emergence of a conflict situation and conflicting speech activity, leading to the use of invective vocabulary, is due to the fact that communicants enter into a verbal conflict by intentionally insulting and discriminating against each other. Using the example of invectives, verbal relationships that are formed in conflict discourse are studied, which reflects the cognitive aspect of human activity. It is concluded that the largest amount of invective vocabulary is in the category of zoosemantic phraseological units and metaphors and consists of words directly aimed at discriminating against a person’s personality.